Rotary friction welding of 304 stainless steel: parametric study, mechanical properties, and microstructure of the joint - Firmanto, Hudiyo; Candra, Susila; Hadiyat, Mochammad Arbi (Politeknik Negeri Lhokseumawe, 2024)
In the rotary friction welding process, the selection of process parameters affects the friction, heat generation, and joint formation. These factors collectively cause microstructural changes that determine the mechanical properties of the joint. Therefore, the process parameters, microstructure, and mechanical properties were interconnected during rotary friction welding. This study examined the influence of process parameters on their correlation with microstructure and mechanical properties in the rotary friction welding of 304 SS. A 3×4 full factorial experimental design was used to evaluate the effects of the process parameters on the microstructure and strength of 304 SS joints produced through rotary friction welding. An accurate evaluation of joint strength was performed using the notch tensile test technique. The joint with the highest strength was achieved by applying a combination of friction pressure and friction time at 55 bars and 3 seconds, respectively, resulting in a welding efficiency of 103.6%. A very low friction time (i.e., 5 s) produced a weak joint, which should be avoided. The welding process created three distinct structural zones in the joint: a joint structure finer than the parent metal structure, a partially deformed structure, and a heat-affected zone with deformation. Hardness tests of the joints showed a high hardness in the deformed structure. The formed structure contributes to the resulting joint strength.